Rancang Bangun Prototype ESP untuk Pengendapan Debu Limbah Industri dengan menggunakan Transformator Flyback - Achmad Fiqih Fathony (Sains Data Jurnal Studi Matematika dan Teknologi, 2023)
In this study ElectroStatic Precipitator (ESP) is one of the alternative dust catchers with high efficiency (reaching above 90%) and the range of particles obtained is quite large. The purpose of this research is to know the process of making ESP prototypes, to know how flyback transformers work as high voltage suppliers on ESP prototypes and to know the capture of industrial waste dust. This research uses experimental engineering methods. The shape of the prototype electrostatic precipitator is made using materials from acrylic, wood, and paralon 2 1/2 dim. From the results of testing and efficiency calculations on electrostatic prototype precipitators that have been conducted. The working principle of this tool when the control circuit switch on to the EC Centrifugal Fan will work for 40 seconds, the speed of the EC Centrifugal Fan can be set by rotating the potensio meter in the controller room. After 40 seconds EC Centrifugal Fan will ma. After 40 seconds the EC Centrifugal Fan will die and the hammer motor will work for 20 seconds to knock out the dust attached to the CE plate.